EFFECTIVE TECHNIQUES IN TEACHING VOCABULARY FOR ESP LEARNERS (Western European Journal of Linguistics and Education, 2025)
The need for teaching English effectively is an incentive for teachers to rethink and develop new teaching methods. Teachers nowadays have to apply different strategies and new approaches to meet students’ needs and to organize effective classroom. It should be noted, that these new strategies and approaches are sometimes coupled with old methods to reach the desired effect. Considering new approaches, teachers also need to preserve old methods, by applying them differently, in a new light